2009
DOI: 10.1097/qad.0b013e3283262a8d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of classic Kaposi's sarcoma in HIV-negative patients treated with the HIV protease inhibitor indinavir

Abstract: HIV protease inhibitors have been shown to exert antiangiogenic and antitumor actions independently from their antiretroviral effect. Based on these studies, HIV-seronegative patients with classic Kaposi's sarcoma were treated with indinavir and followed for clinical evolution, drug pharmacokinetics and Kaposi's sarcoma biomarkers. A favorable clinical course was associated with high drug plasma levels, reduced production of basic fibroblast growth factor, lower numbers of circulating endothelial cells, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…In western countries, KS incidence has remarkably diminished as the implementation of highly active anti-retroviral therapy. This strategy, that allows immune rescue and Human immunodeficiency virus (HIV) replication control, frequently leads to clinical regression of most KS lesions without the need for specific chemotherapies (Sgadari et al, 2002;Monini et al, 2009). However, although KS tends to decline upon antiretroviral treatment, paradoxical aggravations have been described during the early treatment period, where recovery is generally slow (Mitsuyasu, 2000;Maurer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In western countries, KS incidence has remarkably diminished as the implementation of highly active anti-retroviral therapy. This strategy, that allows immune rescue and Human immunodeficiency virus (HIV) replication control, frequently leads to clinical regression of most KS lesions without the need for specific chemotherapies (Sgadari et al, 2002;Monini et al, 2009). However, although KS tends to decline upon antiretroviral treatment, paradoxical aggravations have been described during the early treatment period, where recovery is generally slow (Mitsuyasu, 2000;Maurer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…7, 24, 27, 28, 49, 52-54 One uncontrolled trial of indinavir suggested a clinical benefit for classic (HIV-negative) KS. 55 Indinavir, ritonavir, lopinavir and other PIs have anti- angiogenic and anti-tumor properties, though they appear to be less potent than nelfinavir and lack anti-HHV-8 activity in vitro . 33, 34 As such, KS treatment and prevention trials should be considered to specifically evaluate nelfinavir or other agents with inhibitory activity against HHV-8.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their pre-clinical findings, Monini et al conducted a pilot trial of indinavir for endemic (HIV-negative) Kaposi sarcoma [76]. Twenty-eight patients received 800 mg of indinavir BID for 12 months, and although a control group was not included, clinical response was associated with blood levels of indinavir.…”
Section: Clinical Oncology Trials (Table 2)mentioning
confidence: 99%